Behavioral Economics as a New Economics Field - Ibragimovich, Berdiev Gayrat; kizi, Sheralieva Farangis Narzulla (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Behavioral economics joined science as a new avenue in the 1970s and 1980s. The article covers the essence, historical evolution, and theoretical underpinnings of behavioral economics, as well as theoretical and practical aspects connected to behavioral economics. The parallels and contrasts between the theories advanced by members of the behavioral economics school and those of classical economics are explored, as well as economic decision-making and its efficacy. The author recommends having scientific and practical expertise in integrating behavioral economics principles to economics.